Hubungan Aktivitas Fisik dengan Kualitas Tidur pada Mahasiswa Kedokteran Universitas Cenderawasih - Ayorbaba, Novia Adeltje; Victor John Sembay, Jimmy Victor John; Astawa, Gregorius Adista Enrico; Christiani, Yemima Wandia; Watofa, Yosefina Marijke (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Sleep is a biological process that is essential for optimal life and health. Poor sleep quality can be experienced by everyone, including students. During their studies, medical students tend to experience problems with sleep quality due to heavy academic demands and busy lecture schedules. One way to improve and enhance sleep quality is by doing physical activity. This study aims to determine the relationship between physical activity and sleep quality in medical students at Cenderawasih University. Methods: This study used a quantitative analytic survey design with a cross-sectional approach. The sample in this study was taken from medical students of Cenderawasih University class of 2023 and 2024 who met the inclusion and exclusion criteria. The instruments in study were the Global Physical Activity Questionnaire (GPAQ) and the Pittsburgh Sleep Quality Index (PSQI). A total of 206 students participated in the study. The majority had moderate physical activity levels (47.6%) and poor sleep quality (88.35%). The Chi-Square analysis test revealed no statistically significant relationship between physical activity and sleep quality (p = 0.764). There is no significant association between physical activity and sleep quality among medical students at Cenderawasih University. Although many students reported moderate levels of physical activity, other factors may influence their sleep quality. Abstrak. Tidur merupakan proses biologis yang penting untuk kehidupan dan kesehatan yang optimal. Keadaan kualitas tidur yang buruk dapat dialami oleh setiap orang termasuk mahasiswa. Dalam menjalani masa studi, mahasiswa kedokteran cenderung mengalami masalah dengan kualitas tidur dikarenakan tuntutan akademik yang berat dan jadwal perkuliahan yang padat. Salah satu upaya untuk memperbaiki dan meningkatkan kualitas tidur adalah dengan melakukan aktivitas fisik. Penelitian ini bertujuan untuk mengetahui hubungan aktivitas fisik dengan kualitas tidur pada mahasiswa kedokteran Universitas Cenderawasih. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain survei analitik cross sectional. Sampel penelitian diambil dari mahasiswa kedokteran Universitas Cenderawasih angkatan 2023 dan 2024 yang memenuhi kriteria inklusi. Instrumen penelitian yang digunakan adalah Global Physical Activity Questionnaire (GPAQ) dan Pittsburgh Sleep Quality Index (PSQI). Penelitian melibatkan 206 mahasiswa. Hasil penelitian menunjukkan mayoritas mahasiswa tergolong memiliki aktivitas fisik sedang yaitu sebanyak 98 orang (47,6%) dan kualitas tidur buruk yaitu sebanyak 182 orang (88,35%). Hasil uji statistik Chi-Square diperoleh nilai p = 0,764 yang berarti tidak terdapat hubungan yang bermakna antara aktivitas fisik dengan kualitas tidur pada mahasiswa kedokteran Universitas Cenderawasih.